Efektivitas Teknik Konseling Cognitive Behavioral untuk Meningkatkan Self-Efficacy Siswa pada Pelajaran Matematika - S Sopiyah; Juntika Nurikhsan; Anne Hafina (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2020)
This paper discusses the effect of CBT in improving students’ low self-efficacy on mathematics. Method being used was quantitative as well as single subject approach with A-B design. The target group being used were students of XI-MIA class. Results of research indicated that CBT was effectively improved students’ self-efficacy on mathematics. Students’ self-efficacy of post intervention was higher than pre intervention of CBT for each single subject of study. The authors recommended for the counseling teachers to use CBT as one of the techniques to improve students’ self-efficacy on mathematics. The teacher of mathematics were also expected not only delivered mathematical contents, but also are expected to strengthen students’ beliefs and self-efficacy on mathematics. For the following researchers, we would like to suggest to enlarge subjects not only for senior secondary classroom, but also for junior high school and primary school classroom. Suggestion also were addressed for subjects other than mathematics that students have lower self-efficacy, and with group setting.